Differential diagnosis of tuberculous and malignant pleural effusions: comparison of the Th1/Th2 cytokine panel, tumor marker panel and chemistry panel. (1st July 2020) - Zhang, Jiang; Chen, Yili; He, Guodong; Jiang, Xiaobing; Chen, Peisong; Ouyang, Juan
Abstract: The differentiation between tuberculous plural effusion (TPE) and malignant plural effusion (MPE) remains a major clinical challenge in the diagnosis and management of pleural effusions, especially in developing countries with a high incidence of tuberculosis. We aimed to evaluate the diagnostic value of cytokines, tumor markers and biochemical markers in the differentiation of TPE and MPE. Two hundred and forty-two patients were included, of whom 134 were diagnosed with MPE and 108 were diagnosed with TPE. In total, 12 markers were tested in pleural effusion samples from all subjects: Interleukin-2 (IL-2), Tumor necrosis factor alpha (TNF-α), Interferon (IFN)-γ, interleukins-4, 6, 10 (IL-4, 6, 10), cytokeratin-19 fragment (CYFRA 21-1), carcinoembryonic antigen (CEA), neuron specific enolase (NSE), adenosine deaminase (ADA), lactate dehydrogenase (LDH) and high sensitivity C- reactive protein (Hs-CRP). The diagnostic value of each marker was evaluated and compared by receiver operating characteristic (ROC) curves. In the 12 markers evaluated, TNF-α, IFN-γ, IL-6, CYFRA 21-1, CEA, ADA and Hs-CRP were significantly different between the TPE and MPE groups, and the areas under the ROC curves were 0.624, 0.942, 0.619, 0.808, 0.903, 0.842 and 0.917, respectively. IFN-γ showed a better diagnostic performance than the other markers. With a cut-off value of >2.45 pg/mL, the sensitivity and specificity of IFN-γ were 91.11 and 91.94%, respectively. TNF-α, IFN-γ, IL-6, CYFRA 21-1, CEA, ADA and Hs-CRP were useful in the differentiation between the TPE and MPE groups. IFN-γ showed a better diagnostic performance than the multitude of other markers evaluated in this study, which is satisfactory for the discrimination of TPE and MPE.